The Olfactory Threshold of Rotundone in Brandy is Ten-fold Higher than in Wine and does not Increase with the Complexity of the Matrix - Geffroy, O.; Aymard, F.; Cuif, C.; Baerenzung dit Baron, T.; Denat, M.; Jacques, A. (South African Journal of Enology and Viticulture, 2023)
Rotundone is the only known aroma compound imparting a peppery aroma to wine. Its presence has recently been documented in spirits, notably those aged in oak barrels. However, the sensory contribution of rotundone in such alcoholic beverages remains hard to predict, given their high ethanol level. The aim of this study was to estimate olfactory thresholds for rotundone in brandy using three different matrices. Rotundone concentrations in the unspiked samples were 50 ng/L for wine distillate and 135 ng/L for brandy, demonstrating for the first time the presence of rotundone in such spirits and a possible endogenous origin. The olfactory detection threshold was estimated at 103 ng/L in 40% (v/v) ethanol solution, while difference thresholds were 171 ng/L and 189 ng/L in fresh wine distillate and young French brandy, respectively, both standardised at 40% (v/v). These thresholds were 10-fold higher than in wines and did not significantly differ according to the complexity of the matrix. Our results, which are still preliminary and would deserve to be validated with a larger number of samples and using a higher number of panellists, open new fields of investigation for a deeper exploration of the concentration range of rotundone in brandies, particularly those that underwent a longer ageing period in barrels.